Leaching Characteristics of Udipsamment Ameliored by Mineral Soil and Adhesive Polymer - Fibrianty Fibrianty; Eko Hanudin; Azwar Ma’as (JOURNAL OF TROPICAL SOILS, 2022)
Udipsamment  is  characterized  by  sand  fraction  > 95%,  loose,  and  very  high  leaching. This  study  aimed  to determine  the  effect  of  mineral  soil  ameliorants  and  adhesive  polymers  on  the character  of  nutrient leaching  in  Udipsamment.  The  leaching   study  in  lysimeters  used  a completely  randomized  design  with three  replications.  The  treatments  consist  of  bagasse  (B),  mineral  soil included  Inceptisol  (I)  and Vertisol  (V),  and adhesive  polymers included tapioca  1% and 2% (T1  and  T2),  tapioca  dregs  1%  and  2  %  (A1 and  A2),  Polyvinylalcohol  0.1%  and  0.2%  (P1  and  P2).  Combination  of  treatments  are  IB,  VB,  IBT1, IBT2,  VBT1,  VBT2,  IBA1,  IBA2, VBA1 ,  VBA2 , IBP1,  I BP2, VBP1,  and  VBP2.  Observations  were made  before  and  after  leaching.  The  research  showed  that  VBT2  increases moisture-holding  capacity. Amelioration improved the ability of  Udipsamment  to  hold  nutrients,  after leaching  for  six  months,  there was  a  decrease  in  organic  C,  total  N,  and  available  P  compared to before  leaching.  Amelioration increased the  soil  CEC,  even up  to  the  sixth  month  leaching,  the soil  CEC  showed  a  higher value  than  before  leaching.  The  amount  of  clay  fraction  was  relatively  uniform  between  the  surface  and  the  bottom of  the lysimeter,  indicating that   the adhesive   polymer  successfully  bonding  the  clay-sand  particles  and prevented clay leaching.